Health for all: the urgent need of health by the people concept - Muzief Munir (Paediatrica Indonesiana, 1981)
lndonesia which consists of more than 13.000 islands has 147 minion population distributed 900 inhabited tislands.Around 66% of the total population live an Java which is only 7% of Indonesia's total land area. As in other developing countries, 80% of her population live in rural areas, and 40% of the total populaton consist of the vulnerable groups namely children under five of age and women in the child bearing age.